The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12254-020-00649-2
|View full text |Cite
|
Sign up to set email alerts
|

A case report on the long-term survival of a patient with HER2-positive metastatic gastric adenocarcinoma and a short review of the current literature

Abstract: Summary The prognosis of patients with metastatic gastroesophageal cancer remains poor despite numerous promising clinical trials, and the clinical benefit of systemic therapies is under critical review. This case report of a patient with human epidermal growth factor receptor 2 (HER2)-positive metastatic gastric adenocarcinoma is an impulse for the importance of individual decision making and molecular guided treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Even though this was a tremendous success, the overall survival remained poor with a median of 13.8 months [3,4]. However, several case reports and few smaller studies have reported that a subgroup of HER2-positive mGC/mGEJC patients showed prolonged survival for several years under maintenance therapy with trastuzumab alone [5][6][7][8]. To date, a biomarker that reliably identifies this long-term responder to trastuzumab treatment remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this was a tremendous success, the overall survival remained poor with a median of 13.8 months [3,4]. However, several case reports and few smaller studies have reported that a subgroup of HER2-positive mGC/mGEJC patients showed prolonged survival for several years under maintenance therapy with trastuzumab alone [5][6][7][8]. To date, a biomarker that reliably identifies this long-term responder to trastuzumab treatment remains elusive.…”
Section: Introductionmentioning
confidence: 99%